2011
DOI: 10.2135/cropsci2010.06.0325
|View full text |Cite
|
Sign up to set email alerts
|

Results of 25 Years of Upland Rice Breeding in Brazil

Abstract: The objective of this study was to estimate the results ofthe upland rice {Oryza sativa L.) breeding program conducted by the Brazilian Agricultural Research Corporation (Embrapa) and collaborators over the period of 1984 to 2009 covering 25 annual steps of improvement. The best lines generated by this program are evaluated in "value for cultivation and use (VCU) trials." This study used data from 603 VCU trials conducted in seven Brazilian States. The group of lines entering VCU in each year was faken as a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 17 publications
5
83
1
Order By: Relevance
“…The annual genetic progress in grain yield obtained in recent studies with wheat was 0.92% in Brazil (Beche et al, 2014), 0.67% in Canada (Thomas and Graf, 2014) and 1.00% in China (Wu et al, 2014). Similarly, the annual genetic progress in rice was 0.67% in Brazil (Breseghello et al, 2011); however, no genetic progress was observed in the dry-land rice program of the State of Minas Gerais (Borges et al, 2009). Furthermore, for carioca common bean in the State of Minas Gerais, the annual genetic progress was 6.74% (Barili et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The annual genetic progress in grain yield obtained in recent studies with wheat was 0.92% in Brazil (Beche et al, 2014), 0.67% in Canada (Thomas and Graf, 2014) and 1.00% in China (Wu et al, 2014). Similarly, the annual genetic progress in rice was 0.67% in Brazil (Breseghello et al, 2011); however, no genetic progress was observed in the dry-land rice program of the State of Minas Gerais (Borges et al, 2009). Furthermore, for carioca common bean in the State of Minas Gerais, the annual genetic progress was 6.74% (Barili et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
“…For the oat crop, the studies developed by Barbosa Neto et al (2000) in Brazil and by Redaelli et al (2008) in Italy can be emphasized. In addition, the studies with cereals from the same family as wheat (Nedel, 1994;Rodrigues et al, 2007;Cargnin et al, 2008;Oury et al, 2012;Beche et al, 2014;Thomas and Graf, 2014;Wu et al, 2014), rice (Borges et al, 2009;Breseghello et al, 1999Breseghello et al, , 2011DoVale et al, 2012), and popcorn (Ribeiro et al, 2012) can be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic progress studies have been performed with wheat (Nedel, 1994;Rodrigues et al, 2007;Cargnin et al, 2008;Oury et al, 2012;Beche et al, 2014;Thomas and Graf, 2014;Wu et al, 2014;Gummadov et al, 2015) and cereals from the same wheat family, including oat (Barbosa Neto et al, 2000;Redaelli et al, 2008) and rice (Borges et al, 2009;Breseghello et al, 1999Breseghello et al, , 2011DoVale et al, 2012). It is assumed that there was genetic progress for wheat grain yield in RS influenced by homogeneous regions of cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…The breeding program for recurrent selection of upland rice of Embrapa aims to genetically improve the populations for a geographic region that is characterized by diverse soils and climatic conditions (Breseghello et al, 2011;Colombari Filho et al, 2013). Therefore, in the next selection cycles, even if genetic variability is maintained for GY and PH in the CNA6 population due to the strong effect of the G×L interaction, it is still necessary to increase the number of replications and locations in order to obtain selection gains superior to those of previous cycles (Morais Júnior et al, 2015), even when satisfactory selection gains are reached.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, considered the main producer of this cereal among the countries in the Western Hemisphere, the focus of the genetic breeding programs is to increase yield potential by developing superior genotypes, such as cultivars (Breseghello et al, 2011;Colombari Filho et al, 2013). However, to reach the desired genetic gains, it is necessary to choose correctly both the strategies to manipulate the available genetic variability and the methods to be used (Châtel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%